Reengineering the New Product Development on Bieichi Technology – A Technology Which Converts Plastics Into Fuels - Maliki, A.; Chew, B.C.; Rashid, N.I.; Mohd Sam, M.F.; Lau, K.L.; Sukri, F.H. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The purpose of this study was to identify activities involved in implementation of reengineering in new product development process on Bieichi technology. The process consisted of ways in which Bieichi technology could be reengineered and developed in Malaysia. The study used a case study through semi-structured interview sessions with 16 respondents from Ministry of Science, Technology and Innovation (MOSTI), National Solid Waste Management Department (NSWMD) and Syngas Sendirian Berhad (Syngas Sdn. Bhd). The findings yielded that there have 7 process the organizations could use to turn their ideas in reengineering on Bieichi technology into a potential valuable product in the future. Moreover, this study provides guidelines to developers in the development of Bieichi technology. Future study should analyze Bieichi technology in terms of challenges and it’s commercialize values in Malaysia in order to ease the implementation of Bieichi technology in Malaysia in the future.